Answer:
3x^2−8x−3
Step-by-step explanation:
(3x+1)(x−3)
=(3x+1)(x+−3)
=(3x)(x)+(3x)(−3)+(1)(x)+(1)(−3)
=3x^2−9x+x−3
=3x^2−8x−3
The two triangles are congruent it two sides and the included angle of one triangle are respectively equal to two sides and angle of the other triangle
Answer: 98.6 - x ≥ 2 or x - 98.6 ≥ 2
Step-by-step explanation:
Since, the normal temperature = 98.6° F
Also, the temperature that differs from normal by at least 2°F is considered unhealthy.
If the temperature is x degree F,
Then, we have two conditions,
Condition 1 : x > 98.6,
The difference between 98.6 and x = x - 98.6
Then the inequality be,
x - 98.6 ≥ 2
Condition 2 : x < 98.6
The difference between 98.6 and x = 98.6 - x
Then the inequality be,
98.6 - x ≥ 2
Answer:
A) (x-7)/(x+4)
Step-by-step explanation:
(x^2-10x+21)/(x^2+x-12)=[(x-3)(x-7)]/[(x+4)(x-3)]=(x-7)/(x+4)
.......................................